Youth participation in small-scale fisheries, aquaculture and value chains in Africa and the Asia-Pacific - Arulingam, Indika; Nigussie, Likimyelesh; Senaratna Sellamuttu, Sonali; Debevec, Liza (CGIAR Research Program on Fish, 2019)
IWMI, a managing partner of FISH, conducted an assessment of youth participation in SSF, aquaculture and value chains between November 2017 and May 2018. The assessment was conducted in Africa and the Asia-Pacific, with a particular focus on the FISH focal countries of Egypt, Nigeria, Tanzania and Zambia in Africa and Bangladesh, Cambodia, Myanmar and Solomon Islands in the Asia-Pacific. The objectives of this study were to (i) assess the participation of youth in fisheries and aquaculture, including opportunities and challenges for participation, (ii) understand what WorldFish and key partners (government organizations, nongovernmental organizations [NGOs] and others) are doing in the focal countries in relation to youth participation, and (iii) (based on the former two points) provide potential areas for further research that could support improved youth participation in aquaculture, SSF and value chains. In this report, definitions of SSF and aquaculture are adopted from WorldFish.